Impact of a primary care based intervention on breast cancer knowledge, risk perception and concern: A randomized, controlled trial. Issue 6 (December 2015) - Livaudais-Toman, Jennifer; Karliner, Leah S.; Tice, Jeffrey A.; Kerlikowske, Karla; Gregorich, Steven; Pérez-Stable, Eliseo J.; Pasick, Rena J.; Chen, Alice; Quinn, Jessica; Kaplan, Celia P.
Abstract: Purpose: To estimate the effects of a tablet-based, breast cancer risk education intervention for use in primary care settings (BreastCARE) on patients' breast cancer knowledge, risk perception and concern. Methods: From June 2011–August 2012, we enrolled women from two clinics, aged 40–74 years with no personal breast cancer history, and randomized them to the BreastCARE intervention group or to the control group. All patients completed a baseline telephone survey and risk assessment (via telephone for controls, via tablet computer in clinic waiting room prior to visit for intervention). All women were categorized as high or average risk based on the Referral Screening Tool, the Gail model or the Breast Cancer Surveillance Consortium model. Intervention patients and their physicians received an individualized risk report to discuss during the visit. All women completed a follow-up telephone survey 1–2 weeks after risk assessment. Post-test comparisons estimated differences at follow-up in breast cancer knowledge, risk perception and concern. Results: 580 intervention and 655 control women completed follow-up interviews. Mean age was 56 years (SD = 9). At follow-up, 73% of controls and 71% of intervention women correctly perceived their breast cancer risk and 22% of controls and 24% of intervention women were very concerned about breast cancer. Intervention patients had greater knowledge (≥75% correct answers) of breast cancer risk factors at follow-up (24% vs. 16%; p = 0.002). In multivariable analysis, there were no differences in correct risk perception or concern, but intervention patients had greater knowledge ([OR] = 1.62; 95% [CI] = 1.19–2.23). Conclusions: A simple, practical intervention involving physicians at the point of care can improve knowledge of breast cancer without increasing concern. Trial Registration: ClinicalTrials.gov identifierNCT01830933 . Highlights: We conducted a randomized trial to evaluate a breast cancer risk education intervention. We designed the intervention for use in primary care with patients and physicians. Our intervention improved patients' knowledge of breast cancer risk factors. Our intervention did not increase concern about getting breast cancer. Breast cancer risk assessment and education should be integrated into primary care.